DEVELOPMENT OF A SET OF MEASURES TO PROMOTE THE INSTAGRAM PAGE - TALANCHUK, DMYTRO; MARKOVETS, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article presents the results of a study of the development of the page on the social network Instagram. A review of scientific sources that cover data on the promotion of profiles on social networks. To achieve this goal, a universal flowchart of the algorithm of actions was created, which will help to get reactions to the distributed content. The limits of interaction with the content that will help to avoid blocking the page are highlighted and the statistics of the page based on which the research of the social network Instagram was conducted are shown.The growing popularity of the social network Instagram encourages the study of methods to promote the profile This study contains information about methods of promoting the page that does not require money. The flowchart will help start-up bloggers and small businesses that do not have the funds to advertise to gain additional reach of the target audience. This block diagram is universal and does not require special topics of the pages. The shown statistics will prove the efficiency of the created block diagram of the page development algorithm. With the help of the flowchart, users will be able to receive additional hundreds, sometimes thousands, of additional target audience reach and content interactions. A study was conducted to determine the best time to publish content. Properly chosen time increases the chances of greater coverage of people on the social network. To determine the time, a foreign study was analyzed and a new one was conducted based on its own Instagram page and KeyHole resource. The article describes the effectiveness and importance of using correct and thematic hashtags. The use of hashtags, as well as other described methods, will help increase the reach of the target audience. The statistics show the effectiveness of this method of popularizing the page and describe the optimal number of hashtags per post.
Keywords: virtual community; communication; information; user; software; interconnection; information technology; analysis; processing; exchange